New evidence from the Aketala site in the oasis of the Western Tarim Basin, Xinjiang for the prehistoric human-environment interaction - Wenli Zheng; Yuanjie Jiao; Mingmin Zhang; Xi He; Shuting Pu; Yonghao Guo; Zhengchuang Hui; Yanfang Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Organ-on-a-chip approaches for panvascular device evaluation: insights from the FLOW framework - Guanzhao Zhang; Shuting Chang; Yunfan Pan; Xingyu Jiang (Science Bulletin, 2026)

Expanding the Knowledge of the Genetic Spectrum of Primary Ovarian Insufficiency Using a Cohort of 118 Chinese Cases - Yuncheng Pan; Shuting Ren; Jitong Mo; Zixue Zhou; Yiqing Liu; Lang Zhou; Xiaojin Zhang; Yanhua Wu (Phenomics, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

“Brick-and-Mortar” multidimensional sodium alginate composite films reinforced with ginger residue nanocellulose for high-performance biodegradable packaging - Huili Zhang; Meiqi Pan; Chunlin Dong; Fangyang Yuan; Zhilong Yu; Shuting Huang; Lixin Lu (Journal of Environmental Chemical Engineering, 2026)

Optimized one-step pyrolysis synthesis of zinc-modified sludge biochar for enhanced perfluorooctane sulfonate removal from water - Muzi Li; Ranbin Liu; Xiaodi Hao; Dongye Zhao; Xi Cheng; Jian Pan; Tianyuan Xu; Shuting Tian; Yangmo Zhu (Environmental Research, 2026)

Classification of key aerosol types from multiple satellite products in Xinjiang, West China - Honglin Pan; Xia Li; Shuting Li; Maoling Ayitikan; Yuting Zhong (Theoretical and Applied Climatology, 2026)

Laboratory-scale characteristics of micro-slip during fault quiescence and implications for injection-induced reactivation stability - Ning Yang; Peng-Zhi Pan; Shuting Miao; Wenbo Hou (International Journal of Rock Mechanics and Mining Sciences, 2026)

Site-specific PEGylation of recombinant protein SAC-TRAIL and characterization of the effect on antitumor activity - Shuting Pan; Yuguo Dong; Xuedong Wang; Yuhong Ren; Zebo Xiu; Jian Zhang (Molecular Biology Reports, 2025)

Strain Localization in Granite via Optical Fiber Sensing: Effects of Crack Heterogeneity and Stress Relaxation - Shuting Miao; Xiujun Zhang; François Renard; Arno Zang; Pengzhi Pan (Rock Mechanics and Rock Engineering, 2025)
Monotonic triaxial compression and multi-stage relaxation tests were conducted on both pristine and thermally fractured granite core samples to investigate the effect of crack heterogeneity and stress relaxation on strain localization. Full-field strain distributions across the sample surfaces were mapped using Distributed Optical Fiber Sensing in combination with a compact fiber configuration. Experimental results indicate that increased crack heterogeneity enhances both the strength and total strain accumulation of granite sample prior to macroscopic failure under confined conditions. Granite with greater heterogeneity exhibits an earlier onset, more prolonged, and slower progression of strain localization compared to less heterogeneous granite, ultimately resulting in a higher degree of strain localization prior to macroscopic failure. In highly heterogeneous granite, high-strain events are redistributed across the sample, preventing excessive strain localization in specific volumes, whereas in less heterogeneous granite, the strain localization zone remains fixed before system-size failure. Optical microscopic observations confirm that higher crack heterogeneity promotes the further development of pre-existing compact and distributed microcracks during mechanical loading, whereas lower heterogeneity promotes the formation of isolated, long microcracks. Additionally, stress relaxation facilitates subcritical crack growth, promoting strain accumulation in pre-damaged zones and enhancing strain heterogeneity within the granite samples. These findings highlight the significant role of stress state, pre-existing damage zones, and initial crack heterogeneities in governing strain localization and macroscopic failure behavior in the upper crust.

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Quantifying permafrost thawing and its impact on lake storage dynamics in the Qinghai-Tibet Plateau - Shuting Ji; Pan Wu; Lin Chen; Yingjie Yang; Xuehui Pi; Jeffrey M. McKenzie; Xiuyu Liang (Journal of Hydrology, 2025)

Solid membrane-based aqueous lithium extraction and adsorption: Advances, challenges, and prospects - Yueru Yang; Shumin Bi; Faquan Wang; Xinyu Pan; Tianci Yang; Shui Hu; Shuting Tang; Qingxiu Jia (Chemical Engineering Journal, 2025)

The synergistic effect of phototherapy and active substances on hair growth - Shuting Qiu; Zhi Pan; Xiao Jiang; Guowen Lv; Anqi Feng; Hongbo Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

Laboratory Shear Behavior of Tensile- and Shear-Induced Fractures in Sandstone: Insights from Acoustic Emission - Shuting Miao; Peng-Zhi Pan; Arno Zang; Chuanqing Zhang; Hannes Hofmann; Yinlin Ji (Rock Mechanics and Rock Engineering, 2024)

Ruthenium decorated nickel-iron layered double hydroxides (NiFe-LDH) for promoting peroxymonosulfate activation and atrazine degradation - Yu Yin; Shuting Pan; Jiajie Lu; Abdul Hannan Asif; Sheng Cui; Shaobin Wang; Hongqi Sun (Journal of Environmental Chemical Engineering, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Preparation of chromium oxide by hydrothermal reduction of sodium chromate aqueous solution with hydrogen and application to chromite ore processing - Panpan Mu; Hongling Zhang; De'an Pan; Shuting Liang; Taiping Lou; Hongbin Xu (Hydrometallurgy, 2024)

A novel physical hurdle technology by combining low voltage electrostatic field and modified atmosphere packaging for long-term stored button mushrooms (Agaricus bisporus) - Fengyi Liu; Yaozong Xu; Min Zeng; Yijie Zhang; Liao Pan; Jun Wang; Shuting Huang (Innovative Food Science & Emerging Technologies, 2023)

Fgf8P2A-3×GFP/+: A New Genetic Mouse Model for Specifically Labeling and Sorting Cochlear Inner Hair Cells - Yi Pan; Shuting Li; Shunji He; Guangqin Wang; Chao Li; Zhiyong Liu; Mingliang Xiang (Neuroscience Bulletin, 2023)

Mechanism Interpretation of Sub-critical Crack Growth in Beishan Granite Subjected to Cyclic Loading - Shuting Miao; Peng-Zhi Pan; Zhaofeng Wang; Yujie Feng; Qingsong Zheng (Rock Mechanics and Rock Engineering, 2023)

Alkalization-induced disintegration increased redox activity of solid humic acids and its soil biogeochemical implications - Caiqin Wang; Shuting Tang; Hangzhe Chen; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Experimental investigation of damage evolution and fracture mechanism in rocks with a single flaw under stepwise cyclic compression - Shuting Miao; Peng-Zhi Pan; Amin Hekmatnejad; Yuxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Shift of phytoplankton and microbial communities cause seasonal dynamics of odor compounds in Oncorhynchus mykiss cultured in a freshwater reservoir - Shuting Li; Fayi Wei; Xuan Dong; Miaojun Pan; Li Li; Xiangli Tian; Qinfeng Gao; Alan E. Wilson (Aquaculture, 2023)

Associations of urinary and blood cadmium concentrations with all-cause mortality in US adults with chronic kidney disease: a prospective cohort study - Jia Zhang; Xiao Wang; Zhibin Ma; Ying Dang; Yaya Yang; Shuting Cao; Changping Ouyang; Xiaoru Shi; Jinhua Pan; Xiaobin Hu (Environmental Science and Pollution Research, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Protective-mechanism-exclusive thermal stability modes of soil organic matter: Novel implication for wildfire effect on soil organic carbon - Caiqin Wang; Tingfeng Cheng; Shuting Tang; Mengxuan Li; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Affinity-based alleviation of dissolved organic matter (DOM) on tetracycline toxicity to photosynthesis of green algae Chlorella vulgaris: roles of hydrophilic and hydrophobic DOM - Caiqin Wang; Hang Xu; Tingfeng Cheng; Shuting Tang; Daoyong Zhang; Meichao Li; Xiangliang Pan (Environmental Science and Pollution Research, 2023)

Fracture Behaviour of Two Microstructurally Different Rocks Exposed to High Static Stress and Cyclic Disturbances - Shuting Miao; Peng-Zhi Pan; Peiyang Yu; Wenbo Hou (Rock Mechanics and Rock Engineering, 2022)

A New DIC-Based Method to Identify the Crack Mechanism and Applications in Fracture Analysis of Red Sandstone Containing a Single Flaw - Shuting Miao; Peng-Zhi Pan; Shankun Zhao; Jun Han; Petr Konicek (Rock Mechanics and Rock Engineering, 2021)

Experimental Study on Damage and Fracture Characteristics of Beishan Granite Subjected to High-temperature Treatment with DIC and AE Techniques - Shuting Miao; Peng-Zhi Pan; Xingguang Zhao; Changyue Shao; Peiyang Yu (Rock Mechanics and Rock Engineering, 2021)

The Influence of Infilling Conditions on Flaw Surface Relative Displacement Induced Cracking Behavior in Hard Rock - Peng-Zhi Pan; Shuting Miao; Quan Jiang; Zhenhua Wu; Changyue Shao (Rock Mechanics and Rock Engineering, 2020)

Temporal characteristics detection and attribution analysis of hydrological time-series variation in the seagoing river of southern China under environmental change - Lihua Chen; Yan Wang; Billel Touati; Haopeng Guan; Gang Leng; Weifu Liu; Shuting Lv; Shuping Huang; Zihao Pan (Acta Geophysica, 2018)

Enhanced organic phosphorus detection in sediments by foam separation and 31P-NMR - Yuxin Shi; Tengfei Pan; Di Mu; Hongqin Wu; Qingqiang Meng; Shuting Qi (Environmental Chemistry Letters, 2014)